(untitled) (Per Musi, 2021)
This paper presents the results of a cross-sectional study of active Brazilian conductors. Data collection was carried out online through a questionnaire and self-applied assessment tools to investigate aspects of training, work and health impact of the participants’ conducting activity. The results indicate problems in the training regarding health aspects and most realize that the places of activities they use are not satisfactory. The conductors realize that their work has a negative impact on the psychological, physical, vocal and auditory aspects respectively. The perception of pain associated with regency had a significant prevalence in the shoulders, neck and dorsal and lumbar regions. An association was found between complaints and prevalence of pain with specific work characteristics, the type of ensemble in which the conductors perform and the use of podium and piano. In conclusion, the study points to the need for curriculum evaluation in conducting courses regarding the existence of health content and the need to offer the regents solutions to the problems inherent in the work.